2018
DOI: 10.1177/0300060518772222
|View full text |Cite
|
Sign up to set email alerts
|

Association between urinary sodium excretion and coronary heart disease in hospitalized elderly patients in China

Abstract: ObjectiveThis study was performed to evaluate the association between urinary sodium excretion and coronary heart disease (CHD) in hospitalized elderly patients in China.MethodsThe 24-h urinary excretion specimens of 541 patients were collected, and the serum creatinine concentration and urinary sodium/potassium ratio were measured. Associations were explored by multivariate logistic regression analysis.ResultsThe mean 24-h urinary sodium excretion was 200.4 mmol, corresponding to 11.7 g of salt intake. Both o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The weekly search identified 4141 citations over the period from April 3 to October 30, 2018, of which 19 studies including dietary sodium and health outcomes met the criteria for full review (Table ). These included systematic review and meta‐analyses (n = 2), randomized controlled trials (n = 3, including one post hoc analysis of a randomized controlled trial), a non‐randomized controlled trial (n = 1), prospective cohort studies (n = 4), a retrospective cohort study using population data (n = 1), and cross‐sectional studies (n = 8) . Two studies assessed mortality outcomes, four studies assessed morbidity outcomes, and one study assessed symptoms/quality of life/functional status outcomes .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The weekly search identified 4141 citations over the period from April 3 to October 30, 2018, of which 19 studies including dietary sodium and health outcomes met the criteria for full review (Table ). These included systematic review and meta‐analyses (n = 2), randomized controlled trials (n = 3, including one post hoc analysis of a randomized controlled trial), a non‐randomized controlled trial (n = 1), prospective cohort studies (n = 4), a retrospective cohort study using population data (n = 1), and cross‐sectional studies (n = 8) . Two studies assessed mortality outcomes, four studies assessed morbidity outcomes, and one study assessed symptoms/quality of life/functional status outcomes .…”
Section: Resultsmentioning
confidence: 99%
“…50 In particular, the use of inadequate sodium intake assessment in observational studies is problematic. Six studies used spot urine collections to estimate usual sodium intake, 24,29,33,35,36,40 despite the large body of literature showing that spot urine collections lack precision and accuracy for assessment of usual sodium intake in individuals. 51,52 The risk of misclassification is high in these studies as demonstrated by Bland-Altman analyses consistently…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the event of excessive pressure overload (hypertension) duration, irreversible fibrosis of the left ventricle will occur, resulting in permanent systolic function impairment. 2 Coronary heart disease has a high incidence in the elderly 3 , and it is clinically manifested as myocardial hypoxia, myocardial ischemia, infarction and other symptoms. It has been shown in most studies that hypertensive patients with coronary artery disease have a significantly higher incidence of increased left ventricular volume compared with patients with simple hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is defined as a complex disease determined by both environmental and genetic factors. It has become a significant public health problem because of the high prevalence and increased risk of cardiovascular and renal diseases [1]. Salt intake plays a critical role among environmental factors; a lot of studies from animals and clinic trials reveal a positive relation between salt intake and hypertension [24].…”
Section: Introductionmentioning
confidence: 99%